2007
DOI: 10.1261/rna.689007
|View full text |Cite
|
Sign up to set email alerts
|

An Hfq-like protein in archaea: Crystal structure and functional characterization of the Sm protein from Methanococcus jannaschii

Abstract: The Sm and Sm-like proteins are conserved in all three domains of life and have emerged as important players in many different RNA-processing reactions. Their proposed role is to mediate RNA-RNA and/or RNA-protein interactions. In marked contrast to eukaryotes, bacteria appear to contain only one distinct Sm-like protein belonging to the Hfq family of proteins. Similarly, there are generally only one or two subtypes of Sm-related proteins in archaea, but at least one archaeon, Methanococcus jannaschii, encodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
90
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 61 publications
2
90
0
1
Order By: Relevance
“…In contrast, no apparent phenotype emerged from an hfq knockout in Staphylococcus aureus (Bohn et al, 2007). Although not all eubacterial genomes encode an Hfq protein, an Hfq-like protein has recently been identified in Archaea (Nielsen et al, 2007). Importantly, although this Methanocaldococcus jannaschii protein differs from the well-characterized eubacterial Hfq proteins in length and amino acid sequence, it does restore complex phenotypes to an E. coli hfq deletion strain (Nielsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, no apparent phenotype emerged from an hfq knockout in Staphylococcus aureus (Bohn et al, 2007). Although not all eubacterial genomes encode an Hfq protein, an Hfq-like protein has recently been identified in Archaea (Nielsen et al, 2007). Importantly, although this Methanocaldococcus jannaschii protein differs from the well-characterized eubacterial Hfq proteins in length and amino acid sequence, it does restore complex phenotypes to an E. coli hfq deletion strain (Nielsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hfq is a member of the Sm and Sm-like family of proteins found in all three domains of life (45) and forms a homohexameric structure that binds preferentially to A/U-rich RNAs (reviewed in references 6 and 67). Hfq serves as posttranscriptional regulator that binds small RNAs (sRNA) and mRNAs and facilitates their interaction (1,22,37,60).…”
mentioning
confidence: 99%
“…Since A-rich sequences are common in mRNAs while U-rich sequences are present at the 3 0 -end of most sRNAs, it is believed that Hfq binds simultaneously to an sRNA and an mRNA and thereby facilitates their pairing. Crystal structures of Hfq from several Gram-positive and Gram-negative bacteria, including Escherichia coli, have already been presented in the literature (Schumacher et al, 2002;Sauter et al, 2003;Nikulin et al, 2005;Nielsen et al, 2007;Bøggild et al, 2009;Link et al, 2009;Baba et al, 2010;Moskaleva et al, 2010;Beich-Frandsen, Večerek, Konarev et al, 2011;Sauer & Weichenrieder, 2011;Kadowaki et al, 2012;Someya et al, 2012;Wang et al, 2013;Yonekura et al, 2013;Robinson et al, 2014). Recent structural studies on Salmonella typhimurium Hfq also revealed RNA binding to the proximal binding site of Hfq and demonstrated that the free 3 0 -hydroxyl group at the end of the RNA is critical for RNA binding and 3 0 -end recognition (Sauer & Weichenrieder, 2011).…”
Section: Introductionmentioning
confidence: 99%